Análisis del empleo en el Ecuador frente al dinamismo de la economía digital durante el estado de excepción por COVID 19 - Bosquez Suarez, Guido Hugo (2021)
The restrictive measures of confinement and social distancing implemented to curb the spread of Covid-19 during the state of emergency hit the national and international economy hard. This event marked a historical milestone that paralyzed the association modalities and slowed down the production supply. Given this scenario, "Analysis of employment in Ecuador in the face of the dynamism of the digital economy during the State of Emergency due to COVID 19", presents a detailed study of the economic impact that the health measures to curb the pandemic had on the labor market and, at the same time, it exposes the prominence that the digital economy registered in the face of governmental restrictions on mobility. In order to meet the research objectives, exploratory and descriptive research with a mixed qualitative and quantitative approach was used...........